Abnormal Brain-Derived Neurotrophic Factor Exon IX Promoter Methylation, Protein, and mRNA Levels in Patients with Major Depressive Disorder - Hsieh, Men-Ting (J Clin Med, 2019)
Brain-derived neurotrophic factor (BDNF) exon IX promoter methylation levels, serum BDNF protein levels, and serum mRNA levels were investigated in patients with major depressive disorder (MDD) and healthy controls. Over two years, 51 patients with MDD and 62 healthy controls were recruited. Peripheral blood was drawn from all participants to analyze the BDNF exon IX promoter methylation levels as well as serum BDNF protein and mRNA levels, at baseline and after four weeks of antidepressant treatment. Methylation sequential analysis showed that patients with MDD (n = 39) had a higher methylation level at CpG site 217 and lower methylation levels at CpG site 327 and CpG site 362. Drug responders (n = 25) had a higher methylation level at CpG site 24 and CpG site 324 than the non-responders (n = 11). Patients with MDD had a lower serum BDNF protein and mRNA levels than the healthy controls. In conclusion, these results showed that BDNF exon IX promoter methylation levels, serum BDNF protein level, and serum BDNF mRNA level could contribute to the pathophysiology of a major depressive disorder.